ANALYSIS OF THE MARKET OF FRUIT AND BERRY WINES AND FERMENTATION ACTIVATORS - Lapytska, Надія; Berezhniak, Кароліна (Biota. Human. Technology, 2023)
The paper presents the results of analytical studies of the world market of alcoholic products and established the share of fruit and berry wines on it. The assortment of fruit and berry wines on the world market was analyzed and it was concluded that the largest producers of this product category are England, Ireland and Germany. It has been established that apple ciders are the most popular among fruit wines, and also plums are used mainly in Japan for the production of such drinks. During the analysis of literature data, it was established that Ukraine has a strong potential for the production of fruit wines, because the yield of garden crops in our country is increasing every year, while in Europe it is decreasing. In order to ensure the nutrition of yeast and activation of alcoholic fermentation in the production of fruit and berry wines, it is proposed to consider the possibility of adding wheat germ meal. Due to the content of protein in the amount of 45% g in the proposed raw material, the nitrogen nutrition of yeast is improved, and due to the presence of easily digestible sugars, 100 g of which contains 20.8 g of glucose, 23.7 g of fructose, 21.3 g of sucrose and 34.2 g of maltose , the alcoholic fermentation of fruit and berry wort is activated. The purpose of the article was to determine the market share occupied by fruit and berry wines, to analyze their assortment; to study the range of additives used to activate the fermentation of fruit and berry wort and to establish the possibility of using wheat germ meal in the production of fruit and berry wines. Methodology. Analytical, physical and chemical research methods were used during the work. Processing of the results was carried out using databases “MC Excel databases”. The scientific novelty consists in the fact that the world market of fruit and berry wines has been studied and the assortment of these drinks by manufacturers has been systematized; the assortment of additives used for the purpose of nitrogen nutrition in fruit and berry winemaking was systematized and the carbohydrate composition of wheat germ meal was analyzed as a promising raw material for the activation of alcoholic fermentation of fruit and berry wort. Conclusions: the assortment of fruit and berry wines on the world market, including in Ukraine, has been studied and systematized; the assortment of additives used as nitrogen nutrition for yeast in fruit and berry winemaking was studied and systematized; the prospects of using wheat germ meal as an activator of alcoholic fermentation have been established.